Soil Improvement through Anogeissus pendula Based Agroforestry System - Rai, A.K.; Solanki, K. R.; Rai, P. (Indian Journal of Agroforestry, 2020)
Studies conducted with five genotypes of A. pendula (AP-12, AP -28, AP-35, AP-52 and AP-S2) to know the comparative performance of agri-silvicultural system and sole cropping on soil amelioration under rainfed in semi-arid region at Jhansi. Results revealed that improvement in soil nutrients were observed under both agri-silvicultural system as well as sole cropping as compared to initial value of soil, However, improvement in soil nutrients in agri-silvicultural system was more pronounced as compared to sole cropping except available potassium, Although, there was no systematic trend among the genotypes regarding the soil improvement. Â